[PP.25.20] RARE CASE OF PHEOCHROMOCYTOMA ASSOCIATED WITH BENIGN THYROID NODULE. (September 2016) - Nitulescu, A.; Ianula, R.; Gheghici, S.; Homentcovschi, C.; Siliste, R.; Chioncel, V.
Abstract : Objective: Pheochromocytomas are rare tumours originating in chromaffin cells, representing 0.1–1% of all secondary hypertension (HT) cases. The majority are benign and unilateral, characterized by production of catecholamines and other neuropeptides. Mainly located in the adrenal gland, they are more frequent between the 3rd and 5th decades of life; however, 10–25% can be associated with genetic familial syndromes, type 1 neurofibromatosis and Von-Hippel-Landau disease. The authors present a rare case of secondary HT due to a pheochromocytoma. Design and method: A 43-year-old female patient presented with palpitations, diaphoresis and headaches associated with severe hypertension (BP up to 230/120 mmHg), occurring more frequently and becoming more severe since they began (6 months before presentation). Differential diagnosis for secondary hypertension was considered. Clinical suspicion of pheochromocytoma was confirmed by serum cathecholamine levels, transabdominal USG and abdominal CT scan (51/45 mm left suprarenal mass). Due to a solitary thyroid nodule identified by echography, thyroid function tests were performed (normal values for TSH and fT4). Ultrasound examination of the nodule was helpful for determining the solid nature, with a following CT scan of the neck and chest. Fine-needle aspiration biopsy was used for definitive diagnosis of the mass, confirming the benign nature. Concomitant hyperparathyroidism compelled genetic testing for the exclusion of MEN2, which was negative. After having two weeks of preoperative preparation with phenoxybenzamine and propanolol, open surgical removal of pheochromocytoma was done. Perioperative fluctuation of BP was well managed by IV fluid overload, intravenous phentolamine, intravenous esmolol and intravenous ephedrine. Results: Postoperative recovery was uneventful and a month after surgery the patient was asymptomatic, with normal BP and serum catecholamine levels. The patient was monitored according to guidelines, due to possible recurrence of the tumor. Conclusions: Pheochromocytoma is a rare cause of hypertension. If the diagnosis of pheochromocytoma is overlooked, the consequences could be disastrous, even fatal; however, if a pheochromocytoma is identified, it is potentially curable, as being one of the causes of surgically correctable hypertension. In the present case, the patient presented also a thyroid tumoral mass and hypercalcemia, requiring a complete screening for type 2 MEN.